Unilateral duplication of great saphenous vein in the leg - a cadaveric case report - M. T., Che Norma; San, Aye Aye; S., Amierul; M. M., Mohamad Aris; Cheah, Pike See; Othman, Fauziah (2016)
Duplication of great saphenous vein in the left leg of 62 year-old male cadaver was observed during routine dissection of the lower limb at the Department of Human Anatomy, Universiti Putra Malaysia. The duplication of the great saphenous vein in the left leg was associated with oedematous leg and foot. Furthermore, there was also anterolateral overlapping of the femoral artery over the femoral vein at its beginning in the femoral triangle. This variation is very important to a surgeon who is dealing with coronary artery bypass surgery, awareness in present of recurrence of varicosity after a successful surgery and awareness for vascular radiologist in doing ultrasonography of great saphenous vein and preparing for femoral nerve block.